The science of inheritance in its new style, the Shafi’i school of thought as a model (the first section: the cases of the daughter, the son’s daughters, the husband and the wife, with an explanation of the origin of the issue and the dependency) - Junaid Sharif Abdul (Islamic Sciences Journal, 2024)
ABSTRACT Praise be to Allah, prayer and peace be upon the Messenger of Allah and upon his family and all his companions. The science of inheritance is one of the important sciences, and it is an applied science whose importance stems from many aspects. It is related to the division of money among those who deserve it, and since every Muslim person who dies may possess money, it was necessary to divide it correctly according to Islamic law, so the area of application of this science was wide with the expansion of people’s need to divide money. In spite of the urgent need for this science, what is observed is the lack of mastery among the students of the Sharia, and there may be two reasons behind this matter: the first reason is the lack of specialists who study this science, and the second reason is the old method used in teaching it, in which it is so difficult that it may make the students of science alienate them. I do not pretend to be a master in this science, but what I will write down are reflections that I had for a while, some of which crystallized through my teaching of inheritance for several years, as this allowed me to present this science in a way that I see as smooth with the use of some simple mathematical operations that will facilitate Learning it for students, in my previous research I approached addressing contemporary issues that are urgently needed, and this research is within this approach of research, it is the first section within the topic of inheritance, and it will be followed by two parts, Allah willing.